Reduced Gut Acidity Induces an Obese-Like Phenotype in Drosophila melanogaster and in Mice - Lin, Wei-Sheng (PLoS One, 2015)
In order to identify genes involved in stress and metabolic regulation, we carried out a Drosophila P-element-mediated mutagenesis screen for starvation resistance. We isolated a mutant, m2, that showed a 23% increase in survival time under starvation conditions. The P-element insertion was mapped to the region upstream of the vha16-1 gene, which encodes the c subunit of the vacuolar-type H(+)-ATPase. We found that vha16-1 is highly expressed in the fly midgut, and that m2 mutant flies are hypomorphic for vha16-1 and also exhibit reduced midgut acidity. This deficit is likely to induce altered metabolism and contribute to accelerated aging, since vha16-1 mutant flies are short-lived and display increases in body weight and lipid accumulation. Similar phenotypes were also induced by pharmacological treatment, through feeding normal flies and mice with a carbonic anhydrase inhibitor (acetazolamide) or proton pump inhibitor (PPI, lansoprazole) to suppress gut acid production. Our study may thus provide a useful model for investigating chronic acid suppression in patients.